High density lithium niobate photonic integrated circuits - Li, Zihan; Wang, Rui Ning; Lihachev, Grigory; Zhang, Junyin; Tan, Zelin; Churaev, Mikhail; Kuznetsov, Nikolai; Siddharth, Anat; Bereyhi, Mohammad J.; Riemensberger, Johann; Kippenberg, Tobias J. (Nature communications, 2023)
Photonic integrated circuits have the potential to pervade into multiple applications traditionally limited to bulk optics. Of particular interest for new applications are ferroelectrics such as Lithium Niobate, which exhibit a large Pockels effect, but are difficult to process via dry etching. Here we demonstrate that diamond-like carbon (DLC) is a superior material for the manufacturing of photonic integrated circuits based on ferroelectrics, specifically LiNbO 3 . Using DLC as a hard mask, we demonstrate the fabrication of deeply etched, tightly confining, low loss waveguides with losses as low as 4 dB/m. In contrast to widely employed ridge waveguides, this approach benefits from a more than one order of magnitude higher area integration density while maintaining efficient electro-optical modulation, low loss, and offering a route for efficient optical fiber interfaces. As a proof of concept, we demonstrate a III-V/LiNbO 3 based laser with sub-kHz intrinsic linewidth and tuning rate of 0.7 PHz/s with excellent linearity and CMOS-compatible driving voltage. We also demonstrated a MZM modulator with a 1.73 cm length and a halfwave voltage of 1.94 V. Lithium niobate (LN) is difficult to process via dry etching. Here, authors demonstrate the fabrication of deeply etched, tightly confining, low loss LN photonic integrated circuits with losses 4 dB/m using diamond like carbon as a hard mask.